2014
DOI: 10.4028/www.scientific.net/amr.1019.3
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effective Forging of Titanium Alloy Parts and their Mechanical Properties

Abstract: Both open die and closed die powder compact forging can be used for the consolidation of Ti and pre-alloyed Ti 6Al 4V powders produced by a hydride-dehydride (HDH) process. The approach used is initial cold or warm compaction into cylindrical shapes, or into a specific pre-form shape appropriate for achieving a particular final forged shape. The economic benefit is near net-shape processing with minimum machining required after forging. Manufacturing costs are also minimised by forging a compact, with a suffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
(34 reference statements)
1
5
1
Order By: Relevance
“…The tensile data measured from as-extruded rod (CIP + VS + HP + Extruded in Figure 10) show further enhancement of the material performance under uniaxial loading and here YS, UTS and failure strain values of 971, 1152 MPa and 9-11%, respectively were obtained. In reference to previously published tensile data on PM or ingot Ti-6Al-4V alloy, the level of strength attained in this study for as-extruded material is relatively higher, whereas ductility is lower [4,6,7,[16][17][18]. El-Soudani et al have reported that consolidation of blended Ti-6Al-4V powders through can-less extrusion can provide average YS and UTS in the range 875-926 MPa and 979-1021 MPa respectively, while ductility of the material varies between 13% and 15.4%.…”
Section: Tensile Propertiessupporting
confidence: 77%
See 2 more Smart Citations
“…The tensile data measured from as-extruded rod (CIP + VS + HP + Extruded in Figure 10) show further enhancement of the material performance under uniaxial loading and here YS, UTS and failure strain values of 971, 1152 MPa and 9-11%, respectively were obtained. In reference to previously published tensile data on PM or ingot Ti-6Al-4V alloy, the level of strength attained in this study for as-extruded material is relatively higher, whereas ductility is lower [4,6,7,[16][17][18]. El-Soudani et al have reported that consolidation of blended Ti-6Al-4V powders through can-less extrusion can provide average YS and UTS in the range 875-926 MPa and 979-1021 MPa respectively, while ductility of the material varies between 13% and 15.4%.…”
Section: Tensile Propertiessupporting
confidence: 77%
“…It is suspected that if the as-sintered billet had been directly induction heated in air prior to extrusion, it would have picked up a significant amount of impurity oxygen due to the presence of many open pores. As a guideline, a compact with a relative density greater than 92% of full density (and one which contains pores in the form of closed porosity) results in minimal oxygen pick-up during final consolidation in air [7]. This means that in the future, relatively high open porosity of the as-vacuum sintered Cold isostatic pressed billets might be a potential issue which requires further in-depth attention, particularly if larger billets are to be produced by Cold isostatic pressing pre-alloyed powders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…variations in YS, UTS along and ductility. Overall tensile property data presented here is either similar or inferior compared to the data reported in literature before[4,7,8,13,14] .…”
contrasting
confidence: 45%
“…The restrictions on the use of titanium for more general engineering applications, because of its high cost, is well known and requires no further comment [1][2][3]. Thermomechanical powder consolidation (TPC) processes, such as powder compact extrusion (PCE), are capable of costeffectively producing near fully dense material with a wide range of compositions, microstructures and properties [4][5][6][7][8]. PCE combines traditional powder metallurgy and conventional extrusion technology along with the derived benefits of both processes.…”
Section: Introductionmentioning
confidence: 99%